(untitled) (Medico Legal Update, 2021)
The development of prenatal diagnosis has developed very rapidly over decades. Prenatal screening is applied to a mother with high-risk pregnancy (threatening the life of the fetus), such as a too-old mother or a too-young mother and having a certain disease in her medical history. Up until now, the curative method to treat genetic disorder is still developed and perfected. Therefore, a preventative action during pregnancy is important to do, such as Noninvasive Prenatal Testing (NIPT). NIPT method that is widely developed is the circulating cell-free fetal DNA (cffDNA) testing that can be useful for determining the fetal gender, the identification of specific single-gene disorders, blood type, paternity determination, and the potency of regular use for testing chromosomal abnormalities. The detection of cell-free fetal DNA in the maternal blood circulation provides a new expectation for NIPT, especially preventing the severity of genetic disorders.